Pharmacognostical Profiling of Jasminum grandiflorum Linn. leaves - Arun Mittal,; Satish Sardana,; Anima Pandey, (International Journal of Phytomedicine, 2015)
To evaluate the pharmacognostic characters including macroscopic, microscopic and physico-chemical characters of the leaves of therapeutically important plant Jasminum grandiflorum Linn. Fresh and dried leaf samples were studied macroscopically and microscopically. Preliminary phytochemical screening and physciochemical studies were performed by following WHO recommended guidelines for the standardization of the leaves. The detailed microscopy revealed the presence of multicellular trichomes, xylem tissue, phloem tissue, collenchyma, spongy parenchyma and palisade cells. Physico-chemical parameters such as extractive values, ash values, foreign matter, loss on drying, volatile oil content, swelling index, foaming index, crude fibre content, fluorescent behaviour, microbial contamination, aflatoxin content, heavy metal profile, pH values of drug solution were also determined. Preliminary phytochemical screening showed the presence of carbohydrate, terpenoids, steroids, saponins, flavonoids, tannins & phenolics compounds. Various pharmacognostic characters observed in this study can help in the identification and standardization of leaves of Jasminum grandiflorum Linn.